Analysis of Consumer Trust, Social Norms, and Economic Factors in Purchasing Decisions for Sustainable Products in Bandung City - Sudirjo, Frans; Uyun, Zahrotul; Yusup, Yusup; Putra, Alfa Santoso Budiwidjojo (Westscience Press, 2023)
This research investigates the complex interactions between consumer trust, social norms, and economic factors in shaping purchase decisions of sustainable products in Bandung City. Using quantitative analysis, a sample of 250 participants was surveyed, and data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The Measurement Model confirmed the reliability and validity of the latent constructs, and the Discriminant Validity analysis highlighted the distinctiveness of the variables. Hypothesis testing showed significant relationships between Agricultural Policy, Infrastructure, Market Quality, and Crop Farm Sustainability. The Coefficient Model showed strong explanatory power (R Square = 58.8%), and the Model Fit Test confirmed the adequacy of the model. Our findings contribute nuanced insights for policy makers, businesses, and researchers interested in promoting sustainable consumer behavior in urban areas.